PROBLEMS IN TOURISM AND WAYS TO ENSURE SAFETY IN TOURISM DURING THE COVID-19 PANDEMY - Norchaev Asatullo Norbutaevich, (European Journal of Life Safety and Stability (2660-9630), 2021)
In this article are discussed the current problems of tourism during the COVID-19 pandemic and how to ensure security. At the same time, a number of recommendations were developed on mechanisms to support tourism development during a pandemic and on the work to be done